(untitled) (Applied Biological Research, 2020)
A ‘HUW-234 x HUW-468’ RIL population of wheat was evaluated along with 2 parental checks under normal (NS) and heat stress (HS) environments. Five stress tolerance indices namely SSI, TOL, MP, GMP and STI were used to discriminate the genotypic response in terms of susceptibility and tolerance to heat stress using comparative yield data under stress and non-stress conditions. Among various indices used, the mean value and the minimum and maximum values recorded were 0.972 (0.270 and 1.386) for SSI, 2.469 (0.428 and 5.362) for TOL, 2.781 (1.635 and 4.124) for MP, 2.465 (1.449 and 3.667) for GMP and 0.401 (0.145 and 0.838) for STI, respectively. Yield (YHS) was found positively correlated with GMP (r = 0.752), followed by STI (r = 0.699) and MP (0.416) but negatively correlated with SSI (r = -0.699) and TOL (r = -0.361). Yield (YNS) was found positively correlated with MP (r = 0.923), followed by TOL (r = 0.919), GMP (r = 0.676) and SSI (r = 0.653). Based on this study it is recommended that the genotypes having higher value of GMP and STI should be selected while as the genotypes with higher SSI, TOL and STI should be rejected.